2018
DOI: 10.1186/s13073-018-0570-1
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide siRNA screen identifies a druggable host pathway essential for the Ebola virus life cycle

Abstract: BackgroundThe 2014–2016 Ebola virus (EBOV) outbreak in West Africa highlighted the need for improved therapeutic options against this virus. Approaches targeting host factors/pathways essential for the virus are advantageous because they can potentially target a wide range of viruses, including newly emerging ones and because the development of resistance is less likely than when targeting the virus directly. However, systematic approaches for screening host factors important for EBOV have been hampered by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 68 publications
5
43
0
Order By: Relevance
“…Martin et al reported preliminary effect on several RNA viruses such us Newcastle disease virus, Rabies virus and Influenza A virus [116]. BK polyomavirus is a DNA virus member of polyomaviridae family and causative agent of infectious hemorrhagic cystitis in transplant recipients and of polyomavirus-associated nephropathy (PVAN), a potentially dreadful complication after kidney transplantation.…”
Section: Leflunomidementioning
confidence: 99%
“…Martin et al reported preliminary effect on several RNA viruses such us Newcastle disease virus, Rabies virus and Influenza A virus [116]. BK polyomavirus is a DNA virus member of polyomaviridae family and causative agent of infectious hemorrhagic cystitis in transplant recipients and of polyomavirus-associated nephropathy (PVAN), a potentially dreadful complication after kidney transplantation.…”
Section: Leflunomidementioning
confidence: 99%
“…These data suggest a mechanism of action that may be conserved among several cytoplasmically replicating negative-stranded RNA viruses (NSVs) that share commonalties in their replication cycles, such as replication in cytoplasmic inclusion bodies [10,[21][22][23][24]. Importantly, we also could show that NXF1 is important for the life cycle of EBOV in context of infectious virus [19]. However, the precise function of NXF1 in the EBOV life cycle remained unclear.…”
Section: Introductionmentioning
confidence: 80%
“…Expression plasmids for the RNP proteins, the T7 polymerase and the T7-driven monocistronic minigenomes (pT7-1cis-vRNA-rLuc, pT7-1cis-vRNA-nLuc) have been previously described [19,41]. Plasmids for the expression of N-terminally flag/HA-tagged constructs were generated by insertion of the respective genes (NXF1, p15, NP) into a pCAGGS-flag/HA vector.…”
Section: Plasmids and Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-EBOV activity of DHODH inhibitors such as GSK983 and brequinar is related to depletion of pyrimidine pools [65]. Interestingly, a genetic screen also identified de novo pyrimidine biosynthesis as critical for EBOV replication [67]. Although DHODH inhibitors have been used clinically for other applications, in vivo studies have not demonstrated convincing antiviral activity, possibly because uracil is available systemically in vivo to feed the salvage pathway, overcoming the block to the de novo pyrimidine synthesis pathway [68][69][70].…”
Section: Targeting Filovirus Rna Synthesismentioning
confidence: 99%